Field evaluation of a low‐powered, profiling pCO2 system in coastal Washington. (12th March 2020) - Chu, Sophie N.; Sutton, Adrienne J.; Alin, Simone R.; Lawrence‐Slavas, Noah; Atamanchuk, Dariia; Mickett, John B.; Newton, Jan A.; Meinig, Christian; Stalin, Scott; Tengberg, Anders
Abstract: Summertime upwelling of deep, corrosive waters on the continental shelf of the northern California Current System can exacerbate ocean acidification conditions, providing unsuitable environments for development of calcifying organisms and finfish that are important to the local economy. To better understand the carbonate system in this dynamic region, two recently developed technologies were combined with other sensors to obtain high‐frequency carbon profile data from July 2017 to September 2017. The compact, low‐power sensor package was composed of an optical sensor for partial pressure of carbon dioxide ( p CO2 optode, Aanderaa model #4797) integrated onto a wave‐powered PRofiling crAWLER (PRAWLER). The PRAWLER profiled from 3 to 80 m, stopping at fixed depths for varying lengths of time to allow for p CO2 equilibration. p CO2 derived from a regional empirical algorithm was used to correct optode drift using data at 80 m. Near‐surface adjusted optode p CO2 agreed within 6 ± 42  μ atm to surface p CO2 from a nearby Moored Autonomous p CO2 instrument. Throughout the water column, optode p CO2 compared to algorithm p CO2 within −28 ± 66  μ atm. Overall, optode uncertainty was 35–72  μ atm based on root‐mean‐square errors from all comparison data sets. Errors are attributed to optode calibration, adjustment, algorithm uncertainty, and environmental variability between optode and reference data. Improvements for optode performance within this profiling application include using more stable sensing foils, in situ calibration, and pumped flow over the sensing foil. Additionally, the study revealed undersaturated (corrosive) waters with respect to aragonite below 60 m throughout the deployment that reached up to 40 m by mid‐September.